2014
DOI: 10.1136/jramc-2014-000275
|View full text |Cite
|
Sign up to set email alerts
|

Triage in the Defence Medical Services

Abstract: Triage of patients into categories according to their need for intervention is a core part of military medical practice. This article reviews how triage has evolved in the Defence Medical Services and how it might develop in the context of recent research. In particular, a simple model demonstrates that the ideal sensitivity and specificity of a triage system depends upon the availability of transport and the capacity of the receiving units. As a result, we may need to fundamentally change the way we approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Wartime triage was initially meant to establish surgical priority at a time when this process was the only decisive factor in the prognosis of war casualties. 6 The evolution of war medicine has given rise to the need to prioritize access to other scarce resources such as blood products, diagnostic methods and life-saving interventions prior to surgery. As a result, preoperative and pre-hospital categorization tools have been added to classic surgical triage without replacing it.…”
Section: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Wartime triage was initially meant to establish surgical priority at a time when this process was the only decisive factor in the prognosis of war casualties. 6 The evolution of war medicine has given rise to the need to prioritize access to other scarce resources such as blood products, diagnostic methods and life-saving interventions prior to surgery. As a result, preoperative and pre-hospital categorization tools have been added to classic surgical triage without replacing it.…”
Section: Perspectivesmentioning
confidence: 99%
“…Since prospective research in this area is difficult to conduct, and probably unethical, most information has been obtained during simulation research which may not apply to real conditions. [6][7][8] Analysis of the triage during major incidents may also be difficult because of either small sample size, study heterogeneity, and/or biased selection of studied casualties. 9,10 A systematic review concluded that field triage systems do not perform consistently during mass casualty events.…”
Section: Introductionmentioning
confidence: 99%